1987
DOI: 10.1007/bf00252954
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of vincristine toxicity by Cronassial

Abstract: A mixture of gangliosides (Cronassial) protects against the chronic but not the acute lethal toxicity of vincristine in mice and affords some protection against the acute lethal toxicity of vincristine in chicks. The protective effect of Cronassial appears to be greatest near the LD50 of vincristine and then diminishes as the dose of vincristine increases further. Cronassial does not, however, reduce the vincristine antitumour activity, so that the net effect is an improvement in the vincristine therapeutic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In other experiments [3], it had been observed that doses of Cronassial less than 150 mg/kg were insufficient to give protection against the doses of mitozantrone which were employed in the present experiments. In other experiments [3], it had been observed that doses of Cronassial less than 150 mg/kg were insufficient to give protection against the doses of mitozantrone which were employed in the present experiments.…”
Section: Lewis Lung Carcinomamentioning
confidence: 47%
See 1 more Smart Citation
“…In other experiments [3], it had been observed that doses of Cronassial less than 150 mg/kg were insufficient to give protection against the doses of mitozantrone which were employed in the present experiments. In other experiments [3], it had been observed that doses of Cronassial less than 150 mg/kg were insufficient to give protection against the doses of mitozantrone which were employed in the present experiments.…”
Section: Lewis Lung Carcinomamentioning
confidence: 47%
“…Such studies are however difficult to reproduce in animals because vincristine induces no evident signs of neurotoxicity in most laboratory species even at lethal doses, but in experiments to see if Cronassial could affect the acute or chronic lethal toxicity of vincristine in mice, it was found that Cronassial appeared to afford some degree of protection against the chronic lethal effects of vincristine [3]. Since the mechanism of this protection was difficult to define and appeared to us more related to the haemopoietic or gastro-intestinal rather than the nervous system, it seemed worthwhile to examine the effects of Cronassial on the toxicity and activity of other antitumour drugs, particularly those that are not known to have any major neurotoxic side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Such data could be of clinical relevance, based on prior observations indicating potential therapeutic effects of the same gangliosides in tumor-bearing patients affected by drug-induced peripheral neuropathy [7,18]. Such data could be of clinical relevance, based on prior observations indicating potential therapeutic effects of the same gangliosides in tumor-bearing patients affected by drug-induced peripheral neuropathy [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic administration of purified bovine brain gangliosides has been shown (i) to enhance peripheral nerve regeneration following traumatic injury [11,12]; (ii) to reduce peripheral nerve abnormalities accompanying diabetes [30,32] and, most relevant; (iii) to limit VCR-induced loss of functional peripheral nerve fibers [7]. In addition, these gangliosides have been shown not to affect VCR antimitotic activity in vitro and in vivo [7,18].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous injection of gangliosides has been employed in many countries to treat neuropathies due to their neuroprotective effect and potential to promote nerve repair by enhancing nerve sprouting [11]. As early as in the 1980s, ganglioside treatment was found to be useful in the mitigation of vincristine-associated neuropathy, both in rabbit models and cancer patients [12,13]. Preclinical animal models suggested that porcine GM1 could be effective in the prevention and treatment of paclitaxel-induced neuropathy [14].…”
mentioning
confidence: 99%